2021
DOI: 10.9734/jpri/2021/v33i47a33015
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Odontology Knowledge Analysis among Undergraduates Dental Students in Saudi Aribia

Abstract: Aims: This study aims to measure the knowledge and awareness level towards Forensic odontology and Bite mark analysis among Dental students in Saudi Arabia. Study Design: This is an observational cross-sectional study. Place and Duration of Study: Conducted in Saudi Arabia from July to August 2021. Methodology: The study’s population consisted of Dental undergraduate in Saudi Arabia. Our Inclusion criteria: Male and Female, Private or Public, Dental Intern and dental students in Saudi nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In Saudi Arabia, the field of FD is still miles behind and still in its infancy. Several studies were done in the past in Saudi Arabia, [11][12][13][14][15][16][17][18] yet no one was conducted in the western region of Saudi Arabia. The aim of the study is to fill this gap and assess the knowledge, attitude, practice, and self-reported record for a list of items that are potentially useful to FD among dental professionals including general dentists, specialists, and consultants of different dental specialities in the western region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the field of FD is still miles behind and still in its infancy. Several studies were done in the past in Saudi Arabia, [11][12][13][14][15][16][17][18] yet no one was conducted in the western region of Saudi Arabia. The aim of the study is to fill this gap and assess the knowledge, attitude, practice, and self-reported record for a list of items that are potentially useful to FD among dental professionals including general dentists, specialists, and consultants of different dental specialities in the western region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%